The Role of Hemoglobin A1C in Diabetes Screening and Diabetic Retinopathy - Maria Mercedes Chang Villacreses (MDPI AG, 2021)
Hemoglobin A1C (A1C) is used in various settings. Its performance has not been evaluated systemically. We compared A1C in diagnosis of diabetes with fasting plasma glucose (FPG) and 2-h postchallenged plasma glucose (2hPG) parameters in a cross-sectional cohort in the United Stated. Adult subjects (≥20 years) were identified from the National Health and Nutrition Examination Survey 2005–2016 without a history of diabetes who had BMI, A1C, FPG, and 2hPG (n = 10,416). For comparisons, we calculated the sample weighted prevalence, sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) with subgroup analyses. For the retinopathy study, diabetic subjects with established diabetes who responded to the question of diabetic retinopathy were evaluated (n = 3907). Compared to the FPG/2hPG criteria, A1C ≥ 48 mmol/mol (6.5%) had a low sensitivity at 25.90%, with specificity 99.70%, PPV 84.70%, and NPV 95.70%. Subgroup analyses revealed a lower sensitivity in males (24.52%); the lowest in non-Hispanic White (21.35%), in the third decade (14.32%), and in the BMI < 22.50 kg/m2 group (7.21%). The prevalence of self-reported diabetic retinopathy increased drastically with an inflection point at A1C 48 mmol/mol (6.5%) from 11.52% to 18.32% (p < 0.0001). A1C ≥ 48 mmol/mol (6.5%) should be cautiously used to diagnose diabetes in certain subgroups due to very low sensitivity in certain groups. With the confirmation of the association of increasing self-reported diabetic retinopathy with A1C ≥ 48 mmol/mol (6.5%), the current A1C cutoff is an acceptable value with the understanding of especially low sensitivity in certain subgroups.